Norma tragedia lirica in due atti - Bellini, Vincenzo 1801-1835 (Dynamic, 2005)
Norma, a Druid priestess, has broken her vow of chastity with an enemy of her people, the Roman Proconsul Pollione, who has now turned to another lover. Norma must choose between taking vengeance against him or atoning for her sins.
Interpr. u.a.: Dimitra Theodossiou, Norma. Nidia Palacios, Adalgisa. Carlo Ventre, Pollione. Orchestra e Coro del Teatro Massimo Bellini. Tiziana Carlini [Chorltg.]. Giuliano Carella [Dir.]. Walter Pagliaro [Bühnenegie]. Marco Scalfi [Filmregie]. - Aufn.: Catania, Teatro Massimo Bellini, Juni 2005
Keywords: Chastity -- Drama; Man-woman relationships -- Drama; Sins -- Drama; Film; DVD-Video; Operas